Removable rope formula label - YE WENBIN; XU MIN; YANG MIAOFU (2015)
The utility model provides a removable rope formula label, theftproof protection rope, the theftproof warning circuit that include the shell, can electrically conduct, theftproof protection rope constitutes the partly of theftproof warning circuit, as theftproof warning circuit's warning trigger switch, its characterized in that: theftproof protection rope is connected by detachably protect in the label and by protection device, prevent that it is by illegal dismantlement. The utility model discloses can enough realize the convenient of whole root theftproof protection rope and dismantle, reduce the use cost of rope formula label, dismantle and furtherly not only can protect and is dismantled but also can protect and dismantled unconsciously by illegal by illegal to protect rope formula label simultaneously again to improve security, the reliability of using and avoid the wrong report alert. Furthermore, the utility model discloses a but the dismantlement scheme can also combine together with the flexible regulation scheme of theftproof protection rope, improves the convenience of using, the function and the still wire rope handling and the operation of pegging graft of convenient theftproof protection rope of extension rope formula label.